2021
DOI: 10.4103/jhrs.jhrs_239_20
|View full text |Cite
|
Sign up to set email alerts
|

Current awareness and attitude toward fertility preservation in Indonesia: A nationwide survey among health-care providers

Abstract: Context: Fertility preservation (FP) is necessary for cancer patients who develop infertility due to chemotherapy and radiotherapy. In Indonesia, many systematic steps and long-term continued actions must be taken to establish FP units since there has been an increasing incidence of cancer among people under 45 years old. Aims: This study aimed at a comprehensive evaluation on the awareness and practices of health-care providers (HCPs) toward FP. Settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Decreasing ovarian function due to cancer treatment and having a long-term impact on women before the age of 40 will affect sexual health and function (Ayuandari et al, 2021;Hoven et al, 2021). Decreased sexual function is associated with decreased estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing ovarian function due to cancer treatment and having a long-term impact on women before the age of 40 will affect sexual health and function (Ayuandari et al, 2021;Hoven et al, 2021). Decreased sexual function is associated with decreased estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being implemented for nearly two decades, FP is currently not a routine clinical practice. Healthcare providers rarely consult appropriate information about FP to cancer patients in developing countries [ 233 , 234 ]. In developed countries, it is reported that only 17.5% of otorhinolaryngologists consulted FP to their young cancer patients before undergoing chemotherapy [ 235 ].…”
Section: Future Perspectives Of Fpmentioning
confidence: 99%